Nurse’s Characteristics and Their Understanding Regarding the Compatibility of Mixing Intravenous Drug Preparations in Hospital Settings - Rizky Wiharti, Irda; Karuniawati, Hidayah (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Drug incompatibility can occur in patients in hospital who receive one or more drugs at the same time due to incompatible drug mixing, and the mixture is said to be incompatible if there are precipitates, crystals, visual color changes. This research aims to determine the relationship between nurses' knowledge of incompatibility in mixing intravenous drug preparations, so that collaboration between nurses and pharmacists can occur in administering intravenous drugs and can reduce the occurrence of medication errors, especially when administering intravenous drugs. Subjects and Method: Cross sectional research was conducted in RSUD dr. Soeselo, Tegal, Central Java, November 2023. The research subjects were 152 nurses selected using purposive sampling technique. The dependent variable is knowledge. The independent variables are age, gender, length of work, duration of work, and training. Data was collected using a questionnaire and analyzed using multiple linear regression. Results: The number of survey respondents in this study was 152 people, with the majority being 73.7% female and 26.3% male. The average value of the nurses' age was 31.82 ± SD 5.09 and 6.14 ± SD 3.26 for the length of work of the nurses who took part in this study, and the average duration of work was 10.08 ± 2.00. In the multivariate analysis test, gender, last education, duration of work, length of work, age on knowledge had a p value of >0.005 so there was no significant effect. Conclusion: The majority of nurses still have a poor level of knowledge <75% on several questionnaire items. Apart from that, this research shows that there are still many nurses who do not understand intravenous stability and the stages of intravenous administration, which is shown in the question scores. So the role of clinical pharmacy in monitoring and providing education regarding nurse training regarding drug incompatibility is needed.